Level densities at high spin - Åberg, Sven (Nuclear Physics, Section A, 1988)
Level densities are calculated at high spins in the cranked Nilsson model by a simple counting procedure. At a fixed deformation and angular momentum excited states are created as many-particle many-hole excitations (up to 10p-10h) on the cranked ground state. The method allows for a detailed study of high-spin level densities at low excitation energies, at most about 6 MeV above the yrast state, fully taking into account the coupling of the intrinsic degrees of freedom to the rotation. A Fermi-gas expression for the spin dependence of the level density is derived. It shows a (2I + 1)-dependence at low spins but saturates at higher spins in agreement with the microscopic calculation. However, due to changes in the shell energy the microscopically calculated high-spin level density may change also at higher spins. Generally, we find strong shell effects in the level density. It is pointed out that the level-density parameter, a, cannot alone give a sufficient description of the level density at the considered excitation energies. By calculating the level density at different deformations, the feeding to and decay from superdeformed states in 152Dy is discussed. At high spins the superdeformed nucleus 152Dy is found to have a very low level density. Observed feeding and decay properties of superdeformed nuclei are found to be qualitatively well understood from studies of high-spin level-densities.